THE RELATIONSHIP BETWEEN STRESS AND RECURRENT APHTHOUS STOMATITIS AMONG STUDENTS OF THE DENTISTRY FACULTY OF LAMBUNG MANGKURAT UNIVERSITY - Riky Hamdani; Anita Fitriani; Maharani Laillyza Apriasari (Universitas Airlangga, 2023)
Background: Recurrent aphthous stomatitis (RAS) is a yellowish-white ulcer-shaped lesion in the oral mucosa. The prevalence of RAS is estimated to be 20% of the world population. Based on Basic Health Search Indonesia in 2018, the prevalence of RAS was 8% of all oral health problems in Indonesia. Stress is one of the risk factors for recurrent aphthous stomatitis. Someone who is stressed will experience a decrease in the immune system, resulting in tissue destruction in the oral cavity. Purpose: To analyze the relationship between stress and RAS in Faculty of Dentistry, Lambung Mangkurat University students. Methods: This is analytical observational research with a cross-sectional study design. The study used a simple random sampling technique with a total sample of 57 co-assistants of the Dentistry at Lambung Mangkurat University. RAS was examined using a questionnaire, and the stress level was measured using the Perceived Stress Scale (PSS) questionnaire. The results of the study were analyzed using the chi-square test. Results: The result shows that the stress level suffered by the respondents is mainly in the moderate category, with a percentage of 44%. In comparison, the incident of RAS with positive results is mainly experienced by respondents with a percentage of 70.18%. The analysis using the chi-square test showed a significant relationship between stress and SAR with a significance value of 0.01 (p <0.05). Conclusion: The higher the stress level experienced will increase the risk of developing SAR.